2013
DOI: 10.1038/sj.bdj.2013.426
|View full text |Cite
|
Sign up to set email alerts
|

How do UK dentists deal with adverse drug reaction reporting?

Abstract: Under-reporting of ADRs by healthcare professionals is a recognised phenomenon and GDPs appear to be no exception. The effect of providing additional postgraduate training on ADR reporting should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…This can be attributed to unfamiliarity of the study participants to the PvPI or lack in syllabus of the dental curriculum which covers this topic in detail. Similar results have been reported by Khan et al 15 and Palaian et al 16 among health-care professionals in Nepal and Rajesh et al 17 The low objective knowledge scores among dentists in this study were in agreement with the studies done by Khan et al 15 Contrasting results have been observed in a Graph 1: Term PV as understood by study participants study performed by dentists in the United Kingdom by Yip et al 18 Studies done among medical health professionals of developed countries like the United States and the United Kingdom have shown better knowledge scores. [19][20][21] In the United Kingdom and the United States, most of the medical and dental schools have introduced a yellow card ADR reporting system in the undergraduate syllabus and their skills are also assessed.…”
Section: Discussionsupporting
confidence: 92%
“…This can be attributed to unfamiliarity of the study participants to the PvPI or lack in syllabus of the dental curriculum which covers this topic in detail. Similar results have been reported by Khan et al 15 and Palaian et al 16 among health-care professionals in Nepal and Rajesh et al 17 The low objective knowledge scores among dentists in this study were in agreement with the studies done by Khan et al 15 Contrasting results have been observed in a Graph 1: Term PV as understood by study participants study performed by dentists in the United Kingdom by Yip et al 18 Studies done among medical health professionals of developed countries like the United States and the United Kingdom have shown better knowledge scores. [19][20][21] In the United Kingdom and the United States, most of the medical and dental schools have introduced a yellow card ADR reporting system in the undergraduate syllabus and their skills are also assessed.…”
Section: Discussionsupporting
confidence: 92%
“…A significantly ( P = 0.003) greater awareness about ADR reporting system was observed among dental practitioners with more years in practice, in a study done outside India. [ 21 ] A lack of difference in knowledge and attitudes was observed in other studies involving medical faculty and post graduates. [ 14 17 ] It appears that the undergraduate and post graduate training program are lacking in mentoring the doctors for the task of pharmacovigilance and a comprehensive multi-level approach is required to address this problem.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study from UK found awareness about ADR reporting system in 74.6% of dental practitioners. [ 21 ] Between 30% and 90% of medical doctors have been found to be aware of ADR reporting system in other studies in India. [ 14 15 16 17 18 ] Currently, ADR reporting system is not completely established as India is in the process of implementing PvPI in a phase wise manner across the country.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of dentists in the UK revealed that one reason for the lack of reporting of ADRs by dentists was the rarity of oral adverse effects . Previous suggestions to improve ADR reporting include collaboration between dental and pharmacy industries to target recognition of oral ADRs and the incorporation of pharmacovigilance education into undergraduate dental training . It is also recommended to list oral ADRs separately in the registered product information so they are easily found, as the current convention is to list them in the “gastrointestinal” section.…”
Section: Other Considerationsmentioning
confidence: 99%
“…Although ADRs are underreported throughout the health industry, the contribution by dentists is extremely limited with 47 cases of ADRs reported by dentists in the past decade to the Therapeutic Goods Administration (TGA) in Australia, and dentists have contributed merely 0.1% of ADR reports since voluntary recording began in 1971 . Previous studies have also shown variable awareness and knowledge of ADR reporting by dentists …”
Section: Introductionmentioning
confidence: 98%